2021
DOI: 10.1111/poms.13368
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Labels on Time Slot Choice and Operational Sustainability

Abstract: In this paper, we study the effectiveness of incentives on delivery service time slot choices. In particular, we focus on the use of green labels that specify time slots as environmentally friendly and that intrinsically motivate customers to choose a specific delivery time slot in lieu of price incentives based on extrinsic motivation. We argue that this is important since green labels’ intrinsic nature affects costumer choice in fundamentally different ways than price incentives. We conduct two experiments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…While the research on the standard 'next-day' e-grocery businesses is maturing, researchers have only started to study new delivery trends such as flexible delivery options and on-demand delivery by a deadline. In addition, recent studies have identified new ways to steer customer behavior, for example, by means of green labels (Agatz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the research on the standard 'next-day' e-grocery businesses is maturing, researchers have only started to study new delivery trends such as flexible delivery options and on-demand delivery by a deadline. In addition, recent studies have identified new ways to steer customer behavior, for example, by means of green labels (Agatz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The discussed contributions provide valuable insight into relevant aspects of strategic demand management. Compared to the operational and tactical level, the set of research methodologies is more diverse and includes prescriptive analytics (Bruck et al, 2020;Wagner et al, 2021), simulation and scenario evaluation (Agatz et al, 2021;Boyer et al, 2009;Lin & Mahmassani, 2002;Manerba et al, 2018;Phillipson & van Kempen, 2021;Ramaekers et al, 2018;Ulmer, 2017), and game-theoretic (Belavina et al, 2017;Gümüş et al, 2013) and empirical (e.g., de Magalhães, 2021;Milioti et al, 2020) analyses. We explain this observation by the strong interdependencies of strategic demand management with other domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, an open question is what new business models could emerge from the introduction of such labels and how companies incorporate eco-labeling when negotiating with business partners or in pricing decisions for their products and services. For instance, Agatz et al (2021) analyze the interactions between price and eco-labeling incentives for time slot selection in a home delivery service. They conclude from experiments and simulations that eco-labels are more effective than price incentives in fostering more sustainable customer decisions.…”
Section: Research Directionsmentioning
confidence: 99%
“…For instance, Agatz et al. (2021) analyze the interactions between price and eco‐labeling incentives for time slot selection in a home delivery service. They conclude from experiments and simulations that eco‐labels are more effective than price incentives in fostering more sustainable customer decisions.…”
Section: Research Directionsmentioning
confidence: 99%